Educa juntos: um programa de colaboração ou controle da rede municipal de ensino no Estado do Paraná - Sotelo, Maria Luiza Lourenzini (2024)
In this study, we present a brief history of the origin of federative relations in Brazil, through the forms of collaboration between federated entities to materialize educational policies. The deepening of this analysis comes, above all, in the Educa Juntos Program, implemented in collaboration between the state of Paraná and the Municipal Education networks under the coordination of the State Department of Education and Sports - SEED PR, outlining its objective The expansion of technical and pedagogical support to municipalities and the promotion of collaborative actions in municipal education in the state of Paraná are central. In this sense, the guiding question is: Are the actions of the Educa Juntos Program an opportunity for diagnosis and monitoring aimed at the quality of education in these municipal education networks? The aim of this study is to analyze and discuss the influence of this collaboration regime on municipal education policies, based on actions within the scope of the Educa Juntos Program, through the perception of managers working in the education departments of three municipalities in the western region. from Paraná. From the definition of the general objective, the specific objectives are outlined: Understanding the public policies circumvented by Brazilian cooperative arrangements and their effects on educational policies since the 1988 constitution; analyze the set of actions within the scope of the Educa Juntos Program and how they are consolidated to meet the specificities of basic education in municipal networks, the object of this study; investigate whether the Educa Juntos Program promotes improvements in the quality of teaching, and to define the development of local public policies in the municipalities researched. The research methodology is anchored in the Policy Cycle, by Stephen Ball (2005), with the purpose of understanding the movements and structuring elements that constitute these policies and how they materialize in municipal networks. We will use a qualitative approach, allowing a closer relationship between researcher and object of study. To understand the data, we will rely on Laurence Bardin's Content Analysis, which is concerned with understanding the analyzed data, critically, following three stages: preanalysis, exploration of the material and treatment of results, and inference and the interpretation. In this theoretical essay, with still provisional results, explaining the interfaces between the elaboration, articulation and execution of this policy under a collaborative regime, we have already verified the management capacity installed within the municipal networks, through monitoring, the recognition policy, linked to the indices under the aegis of State regulation for public education in Paraná.